Constraining the Distribution of Photosynthetic Parameters in the Global Ocean - Richardson, Katherine; Bendtsen, Jørgen; Kragh, Theis; Mousing, Erik A. (Frontiers in Marine Science, 2016)
Global and regional ocean primary production estimates are highly dependent on assumptions concerning the photosynthetic potential of the resident phytoplankton communities. Little is known, however, about global patterns in the distribution of photosynthetic potential and their causes. Here, we review existing literature reporting photosynthetic characteristics of natural populations. From this, we formulate hypotheses regarding abiotic and biotic factors of potential importance in determining photosynthetic performance. These hypotheses are then tested using data we have compiled from nearly all major ocean basins on the maximum rate of photosynthesis, PBmax, and the slope of the photosynthesis vs. light curve, αB (both parameters normalised to chlorophyll) as well as standard environmental variables, size fractioned chlorophyll, taxonomic data (to group), size and biovolume data for pico-, nano-, and micro-phytoplankton. In terms of abiotic variables, depth of sampling, temperature and nutrient availability all can be related to photosynthetic parameters. The most important biotic variable influencing photosynthetic performance was found to be community size distribution and the small component (i.e. the proportion of the phytoplankton community passing through a 10 µm filter) is shown to have both higher PBmax and αB than the larger phytoplankton component. A simple model was used to derive best fit values for PBmax (1.53/2.50 µgC l-1 h-1) and αB (0.025/0.040) for the large/small groups in the subset of the data where taxonomic data were available (both surface and sub-surface samples) using fractioned chlorophyll data and bulk community photosynthetic parameters. Non-metric multidimensional scaling (NMDS) was used to relate the distribution of photosynthetic parameters and dominant (by biovolume) phytoplankton groups. High PBmax was recorded in communities dominated by dinoflagellates, small flagellates and, in warmer waters, picoeukaryotes and Synecococcus. Diatom dominated communities exhibited lower PBmax and were associated with high inorganic nutrients and colder temperatures. That photosynthetic parameters appear closely related to community size distributions and taxonomic group provides some hope for improving the parameterization of photosynthetic performance in global ocean primary production estimates as both of these parameters can be made from remotely sensed optical characteristics of surface waters.